Technophobia and the Filipino worker. [article]. - Hechanova, Regina M. .
A survey of 137 workers in five Philippine organizations was made to determine the manifestations and antecedents of technophobia. Technophobia was measured in terms of computer anxiety, thought and attitudes. In terms of computer anxiety, 31 percent of workers had scores that would classify them as a highly or moderately technophobic. However, in terms of computers thoughts, only 3 percent reported high technophobia. A matrix was developed classifying individuals into: technophobes, computer skeptics, reluctant users and computer enthusiasts. Regression analysis was conducted to determine predictive ability of the significant individual and contextual correlates. Non of the variables predicted computer anxiety. However, computer thoughts are predicted by years of computer use and training hours. Computer beliefs were predicted by gender and years of computer use. The results suggest the importance of computer exposure and training. In addition, the contingency approach in dealing with technophobia is proposed based on gender and the nature of computer reactions.